Case report: Clinical and histopathological characteristics of psoriasiform erythema and de novo IL-17A cytokines expression on lesioned skin in atopic dermatitis children treated with dupilumab - Ali, Kamran; Wu, Liming; Qiu, YunMi; Li, Menghua (Frontiers in Medicine, 2022)
Background Atopic dermatitis (AD) is a chronic recurrent inflammatory disease, and dupilumab, a human monoclonal antibody, is the firstly approved biological drug for AD. Psoriasiform erythema (PE) during dupilumab treatment in adults has been reported. This study describes the risk of PE in children after initiation of dupilumab treatment. Objectives To evaluate the de novo cytokines gene expression in the transition of atopic dermatitis symptoms to psoriasiform erythema during dupilumab treatment in children. Methods Two 17-year-old teenage twin patients with AD were included in this study who developed psoriasiform erythema after initiation of dupilumab. The lesional skin biopsy specimens were obtained for the histopathological investigation and RNA Fluorescence In Situ Hybridization (RNA-FISH). Dermoscopy, cytometry (cytokine detection in the blood), and blood investigations were completed for the pedigree and the lesioned descriptions. Results Two twin patients with AD presented with erythematic scaly plaques on the back, scalp, abdomen, and extensor extremities after 20 weeks of dupilumab treatment. The transitional change of AD to psoriasiform erythema treated with dupilumab was observed. Our subjects' dermoscopy showed pinpoint bleeding and white scales on pink background. Histopathology features showed psoriasiform hyperplasia, epidermal hyperplasia (acanthosis), ectatic capillaries, perivascular lymphocytes infiltration, and parakeratosis, with the absence of the granular cell layer. mRNA (RNA-FISH) cytokines gene expression showed a significantly high concentration of IL-17A. Blood investigation results showed a high concentration of (Immunoglobulin E) IgE and Eosinophils, and cytokines detection in blood showed IL-5,6 and IL-17 in one patient; however, only IL-5 in another patient. The dupilumab was discontinued and initiated with Baricitinib. Baricitinib showed a significant reduction in skin lesions. Conclusion Psoriasiform erythema can appear during dupilumab treatment in atopic dermatitis children. Potently, by suppressing skewed Th2 activation in patients with AD, the balance might shift toward Th1/Th17 predominance, and psoriasis develops. Baricitinib is a potential drug for psoriasiform erythema with significant therapeutic effects.